2014
DOI: 10.1093/mnras/stu1122
|View full text |Cite
|
Sign up to set email alerts
|

Abundance analysis, spectral variability, and search for the presence of a magnetic field in the typical PGa star HD 19400

Abstract: The aim of this study is to carry out an abundance determination, to search for spectral variability and for the presence of a weak magnetic field in the typical PGa star HD 19400. High-resolution, high signal-to-noise HARPS spectropolarimetric observations of HD 19400 were obtained at three different epochs in 2011 and 2013. For the first time, we present abundances of various elements determined using an ATLAS12 model, including the abundances of a number of elements not analysed by previous studies, such as… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 41 publications
2
13
0
Order By: Relevance
“…All observations yield NDs in both N and Stokes V . The lack of evidence for a magnetic field in this star is consistent with previous failures to detect magnetic fields in PGa stars (Hubrig et al 2014) as well as their cooler analogues the HgMn stars (Makaganiuk et al 2011). The standard deviation of Bz is 31 G, as compared to 68 G in Nz , with a median error bar of 79 G. Bz and Nz are provided in Table 2.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…All observations yield NDs in both N and Stokes V . The lack of evidence for a magnetic field in this star is consistent with previous failures to detect magnetic fields in PGa stars (Hubrig et al 2014) as well as their cooler analogues the HgMn stars (Makaganiuk et al 2011). The standard deviation of Bz is 31 G, as compared to 68 G in Nz , with a median error bar of 79 G. Bz and Nz are provided in Table 2.…”
supporting
confidence: 87%
“…However, the system's phosphorous lines are dominated by the flux from the B component due to the PGa star's extremely strong phos-phorous lines. We therefore extracted LSD profiles using a 14 kK line mask (see § 6.2) with enhanced P abundances ([P] = −4.5), based on the abundance analysis of the PGa star HD 19400 by Hubrig et al 2014). The mask was cleaned so as to remove all lines obviously blended with telluric lines, interstellar lines, H lines, or lines obviously blended with HD156324Aa's spectrum, with 44 P lines remaining for analysis.…”
mentioning
confidence: 99%
“…This technique allows us to determine the mean longitudinal field strength and demonstrate the presence of the crossover effect and quadratic magnetic fields, and so to constrain the magnetic field topology in more detail than can be done with the LSD and singular value decomposition (SVD) methods. For each line in the sample of metallic lines, the measured shifts between the line profiles in the left-and right-hand circularly polarised HARPS spectra are used in a linear regression analysis in the ∆λ versus λ 2 g eff diagram, following the formalism discussed by Mathys (1991Mathys ( , 1994; see also Hubrig et al 2014a, Fig. 11).…”
Section: Potsdam Reduction and Analysismentioning
confidence: 99%
“…Next, we compare the pair of P and Ga, because a small group of PGa stars sometimes appear in papers (e.g. Hubrig et al 2014) in which both P and Ga are observed to be enhanced. We find in the present study that both P and Ga are definitely over-abundant in 3 Cen A (P [+ 2.0] and Ga [+ 3.3]) while in HD 185330 only P is over-abundant [∼ + 1.8].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to HR 6000, Castelli and Hubrig (2004b) obtained a slight over-abundance of P [+ 0.31] and a large overabundance of Ga [+ 3.7] in HD 175640. Interestingly, in a PGa star HD 19400, both P and Ga show large over-abundances of P [+ 2.3] and Ga [+ 3.8] (Hubrig et al 2014). Thus, we find large scatters in the abundance ratio of P to Ga among Bp stars and there must be some controlling mechanisms to account for observations.…”
Section: Discussionmentioning
confidence: 99%